IN VITRO ASSESSMENT OF BIOPESTICIDE BACILLUS THURINGIENSIS VAR. KURSTAKI HD- 1 EFFECTIVENESS ON PHYTOPHTHORA PALMIVORA, AGENT OF COCOA BLACK POD ROT IN CÔTE D’IVOIRE - Gabaze, Gadji Alahou Andre; Bernard, Yapo Ossey; Kouabenan, Abo; Klotioloma, Coulibaly; Ismael, Kebe Boubacar; Robert, Gnepe Jean; Dayal, Tyagi Rajeshwar (European Scientific Journal, ESJ, 2015)
Phytophthora Palmivora is responsible for the cocoa black pod rot in Côte d’Ivoire, with production losses varying from 20 to 40% depending on the regions. Effectiveness of the environmentally friendly biopesticide Bacillus thuringiensis var. kurstaki HD-1 was evaluated in vitro on the pathogen. The medium pea supercooled has been incorporated with the bioproduct at different concentrations: C1 = 100%, C2 = 50%, C3 =25%, C4 = 12.5% and C5 = 6.25%. This medium into Petri dishes was inoculated either by spreading, with 0.1 mL of P. palmivora inoculum at103 zoospores /mL, or with a mycelial disc of P. palmivora calibrated at 6 mm diameter in the center of the box. The results showed that the germination of zoospores was inhibited at the rate of 100% in the presence of the concentrations C1 and C2. This rate was 74.82 ± 21.53%, 73.17 ± 20.88% and 59.12 ± 39.05%, respectively, for C3, C4 and C5. The efficacy of the bioproduct is revealed by a significant reduction of mycelia growth ranging between 57.77± 2.4 to 100% in the presence of the concentrations C5 to C1. The IC50 of germination was 3.36% of concentration and the IC90 was 43.22%; while those which inhibit 50% and 90% of mycelial growth were 5.67% and 77.94% respectively. The biopesticide Btk HD-1 has a proven fungistatic effect against P. palmivora. Its effectiveness increases with its concentration. So it can be a valuable component of an integrated cocoa black pod management.